Papaya (Carica Papaya L.) Seed Extract as Male Contraception via Decreasing The Quality of Rat's (Rattus Norvegicus) Sperm - Sri Nita; Arum Setiawan; Rara Inggarsih; Uci Tantri; Meryska Hardiana (HM Publisher, 2020)
Background. Population growth needs to be controlled so as not to cause new and serious problems. Pregnancy and birth control is a solution to control this sizable population growth. Contraception is a way to prevent pregnancy, by inhibiting the process of ovulation, fertilization and implantation. Nevertheless, most of contraceptive regiments were aimed to woman. Male contraception nowadays is very rare. Papaya seed is one of the male contraceptive candidates which has the potential to be developed as male contraception. Previous studies have shown the potential of papaya seed extract could reduce the weight of reproductive organs of male white rats, where it was believed that there was a decrease in spermatogenesis activity. Methods. This research was an in-vivo experimental research post-test only with control group. The study used 32 male and healthy rats (Rattus norvegicus) Wistar strain with 8-10 weeks of age. Rats were grouped into 1 control group and 4 treatment groups that were randomly selected. The four treatment groups were group 1: control administered 1% 2ml CMC orally one time per day every morning, group 2: were given N-hexane papaya seed fraction, group 3: were given ethyl acetate papaya seed fraction and group 4: were given ethanol-water papaya seed fraction. The three fractions were given to rats orally at a dose of 100 mg / KgBB / day for 24 days. After that, rat's testes and epidydimis were evacuated to observe reproductive organs and sperm quality. Results. Anatomically, Group 2 and 3 were statistically significant in reducing testicular's and epidydimis' weight compared to the control group, but the n-hexane group was more effective in reducing testicular weight than other treatment groups. Furthermore, groups 2, 3 and 4 were statistically significant in reducing sperm quality (motility, viability, amount of sperm cells and normal sperm cell morphology) compared to the control group, but the n-hexane group was more effective in reducing sperm quality than other treatment groups. Conclusion. Papaya seed n-hexane fraction has potential as a male contraceptive by reducing spermatogenesis activity and decreasing sperm quality in white rats. Keyword : papaya seed, male contraception, rat's sperm